DAMPAK PASAR BLIMBING TERHADAP KINERJA RUAS JALAN BOROBUDUR KOTA MALANG - Rifky primasworo (Universitas Islam Balitar Blitar, 2026)
The road system is one of the essential transport infrastructures for achieving both dynamic and healthy socialstability and economic development. This kind of study employs a quantitative descriptive research design. Theapproach uses side obstruction surveys, vehicle volume surveys, and road geometry surveys. The analysis isconducted using the 2014 Indonesian Road Capacity Guidelines. The Borobudur road section's performance inMalang City indicates that Thursday from 07:0 to 08:00 is peak hour. This is based on a road capacity value (C) of2844.072 skr/hour and a degree of saturation (Dj) value of 1.90 above the Dj value required in the PKJI 2014,which is Dj > 0.85. This means that the service level is F, and in prior years, the service level was F due to anunreliable flow, occasional stops in speed, and demand that was approaching capacity.